Etiology and clinical profile of patients with tall stature: A single-center experience - Alpesh Goyal; Viveka P Jyotsna; Arun K C. Singh; Yashdeep Gupta; Rajesh Khadgawat (Indian Journal of Endocrinology and Metabolism, 2020)
Background: There is no published literature on the profile of patients with tall stature (TS) from India. This study aimed to evaluate the etiological and clinical profile of patients with TS referred to our hospital. Materials and Methods: We performed a retrospective review of records of patients referred to us for evaluation of TS (January 2007 to March 2020). Relevant clinical, anthropometric, biochemical, and radiological data at presentation were recorded, and the final diagnosis reviewed. Results: The study included 16 subjects (6 boys, 10 girls) with a mean age at presentation of 13.2 ± 3.6 years. Most subjects were pubertal (n = 10) and belonged to the overweight or obese category (n = 10). The mean height and height standard deviation score (SDS) were 172.3 ± 20.3 cm and 3.6 ± 1.5, respectively, while mean mid-parental height (MPH) and MPH SDS were 168.8 ± 8.8 cm and 1.2 ± 0.9, respectively. The etiological diagnoses were familial TS (n = 9), acrogigantism (n = 3), obesity-related TS (n = 2), constitutional advancement of growth (n = 1), and Marfan syndrome (n = 1). The mean height SDS in subjects with acrogigantism was 6.4 ± 1.2 compared to 3.0 ± 0.6 in those with other etiologies of TS. Only one girl with familial TS and significantly increased predicted adult height (+4.56 SDS) opted for sex steroid therapy. Conclusion: Familial TS is the most common diagnosis among patients referred for evaluation to our hospital. One should consider the possibility of acrogigantism in patients with growth acceleration, extreme TS, and markedly increased gap between height SDS and MPH SDS. Most patients with familial TS require reassurance and sex steroid therapy should be reserved for highly selected cases.